The role of CD8+ T cells in endometriosis: a systematic review - Kisovar, Ana; Becker, Christian M.; Granne, Ingrid; Southcombe, Jennifer H. (Frontiers in Immunology, 2023)
Background Endometriosis is a chronic disease affecting 6–10% of women of reproductive age. It is an important cause of infertility and chronic pelvic pain with poorly understood aetiology. CD8+ T (CD8 T) cells were shown to be linked to infertility and chronic pain and play a significant role in lesion clearance in other pathologies, yet their function in endometriosis is unknown. We systematically evaluated the literature on the CD8 T in peripheral blood and endometriosis-associated tissues to determine the current understanding of their pathophysiological and clinical relevance in the disease and associated conditions (e.g. infertility and pelvic pain). Methods Four databases were searched (MEDLINE, EMBASE, Web of Science, CINAHL), from database inception until September 2022, for papers written in the English language with database-specific relevant terms/free-text terms from two categories: CD8 T cells and endometriosis. We included peer-reviewed papers investigating CD8 T cells in peripheral blood and endometriosis-associated tissues of patients with surgically confirmed endometriosis between menarche and menopause, and animal models with oestrous cycles. Studies enrolling participants with other gynaecological pathologies (except uterine fibroids and tubal factor infertility used as controls), cancer, immune diseases, or taking immune or hormonal therapy were excluded. Results 28 published case-control studies and gene set analyses investigating CD8 T cells in endometriosis were included. Data consistently indicate that CD8 T cells are enriched in endometriotic lesions in comparison to eutopic endometrium, with no differences in peripheral blood CD8 T populations between patients and healthy controls. Evidence on CD8 T cells in peritoneal fluid and eutopic endometrium is conflicting. CD8 T cell cytotoxicity was increased in the menstrual effluent of patients, and genomic analyses have shown a clear trend of enriched CD8 T effector memory cells in the eutopic endometrium of patients. Conclusion Literature on CD8 T cells in endometriosis-associated tissues is inconsistent. Increased CD8 T levels are found in endometriotic lesions, however, their activation potential is understudied in all relevant tissues. Future research should focus on identifying clinically relevant phenotypes to support the development of non-invasive diagnostic and treatment strategies. Systematic Review Registration PROSPERO identifier CRD42021233304